Digital Storytelling for Environmental Education on YouTube: Findings from Social Forestry Context - Herutomo, Anton; Dhewanto, Wawan; Prasetio, Eko Agus (Jurnal Manajemen Teknologi, 2023)
Abstract. Digital storytelling is a method of telling stories using digital media. This method can be used for educational purposes including environmental education to support sustainability mindset. This study aimed to explore the use of digital storytelling for environmental education on Youtube in the context of social forestry in Indonesia. The research method used was Focus Group Discussion (FGD) and analyses using thematic coding. The findings from 15 professionals and experts in 3 FGD sessions showed that digital storytelling with Youtube can be an effective tool for environmental education. This is because YouTube as a digital storytelling media captures the attention of viewers, helps them understand complex environmental concepts, and promotes alignment to support sustainability. Digital storytelling in YouTube can be used to build relationships and collaboration among viewers in local and regional scope. Keywords: Social innovation, digital storytelling, environmental sustainability, focus group discussion, youtube Abstrak. Digital storytelling adalah metode berkisah dengan menggunakan media digital. Metode ini dapat digunakan untuk tujuan pendidikan termasuk pendidikan lingkungan untuk mendukung pola pikir yang mendukung pelestarian lingkungan. Penelitian ini bertujuan untuk mengeksplorasi penggunaan digital storytelling untuk pendidikan lingkungan hidup di Youtube, dengan konteks perhutanan sosial di Indonesia. Metode penelitian yang digunakan adalah Focus Group Discussion (FGD) dan analisis menggunakan koding tematik. Temuan dari tiga sesi FGD menunjukkan bahwa digital storytelling dengan Youtube dapat menjadi sarana yang efektif untuk pendidikan lingkungan. Ini karena mendongeng digital menarik perhatian pemirsa, membantu mereka memahami konsep lingkungan yang kompleks, dan mendorong keselarasan untuk mendukung keberlanjutan. Berkisah melalui media digital dapat digunakan pula untuk membangun relasi dan kolaborasi antar pemirsa dalam lingkup lokal dan regional. Kata kunci: Inovasi sosial, cerita digital, pelestarian lingkungan, focus group discussion, youtube